Treatment of relapsed/refractory CLL with Venetoclax-Rituximab during the COVID-19 pandemic: A daily-life experience in southern Italy. - Stefano Molica; Paolo Sportoletti; Nicola Di Renzo; Pellegrino Musto; Fabrizio Pane; Francesco Di Raimondo (Mediterranean Journal of Hematology and Infectious Diseases)
With more than 3 million proven infections and 100.000 associated deaths in Italy, the COVID-19 pandemic poses extraordinary challenges to health-care professionals and especially to those caring for patients with haematologic malignancies  (1-2). Given the multiple   immune  defects characterizing chronic lymphocytic leukaemia (CLL), it is considered that patients with this form of leukemia have a high-risk of suffering severe forms of COVID-19 (3-4).